Empowering the Digital Generation:: the Role of Biblical Discipleship in Shaping Christian Identity and Countering Cultural Challenges - Saptorini, Sari; Purnamasari, Citaning; Arifianto, Yonatan Alex (Sekolah Tinggi Teologi Parakletos Tomohon, 2025)
Abstract: The digital generation, particularly Millennials and Gen Z, faces an identity crisis driven by the influence of digital culture, moral relativism, and a lack of strong spiritual foundations. This crisis results in weakened Christian values in daily life, posing challenges in forming a steadfast identity amid globalization. This study explores how biblical discipleship shapes a strong Christian identity and equips the digital generation to face modern cultural challenges. Using a descriptive qualitative approach based on a literature review, this research analyzes the concept of biblical discipleship and its relevance in shaping spirituality and strengthening the faith resilience of the digital generation. The findings indicate that biblical discipleship, rooted in the teachings and example of Christ, fosters confidence, reinforces identity as children of God, and develops Christian character. Relevant discipleship strategies for the digital era, including the use of digital technology and contextual approaches, are necessary to enhance the effectiveness of church ministry. Furthermore, digital literacy and creative content in communicating the Gospel to young generations play a crucial role in strengthening Christian identity. Abstrak: Generasi digital, terutama Millennials dan Gen Z, menghadapi tantangan berupa krisis identitas yang dipicu oleh pengaruh budaya digital, relativisme moral, dan minimnya fondasi spiritual yang kuat. Krisis ini berakibat pada lemahnya nilai-nilai Kristiani dalam kehidupan sehari-hari, sehingga memunculkan tantangan dalam membentuk identitas yang teguh di tengah arus globalisasi. Penelitian ini mengeksplorasi bagaimana pemuridan berdasarkan Alkitab membentuk identitas Kristiani yang kuat dan membekali generasi digital menghadapi tantangan budaya modern. Menggunakan pendekatan kualitatif deskriptif berbasis studi literatur, penelitian ini menganalisis konsep pemuridan Alkitabiah dan relevansinya dalam membentuk spiritualitas serta ketahanan iman generasi digital. Hasil penelitian menunjukkan bahwa pemuridan alkitabiah, yang didasarkan pada ajaran dan teladan Kristus, menumbuhkan rasa percaya diri, memperkuat identitas sebagai anak-anak Allah, dan mengembangkan karakter Kristen. Strategi pemuridan yang relevan untuk era digital, termasuk penggunaan teknologi digital dan pendekatan kontekstual, diperlukan untuk meningkatkan efektivitas pelayanan gereja. Lebih lanjut, literasi digital dan konten kreatif dalam mengkomunikasikan Injil kepada generasi muda berperan penting dalam memperkuat identitas Kristiani.